Profiling of lincRNAs in human pluripotent stem cell derived forebrain neural progenitor cells - Daniela A. Grassi; Per Ludvik Brattås; Marie E. Jönsson; Diahann Atacho; Ofelia Karlsson; Sara Nolbrant; Malin Parmar; Johan Jakobsson (Heliyon, 2020)
Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) can be differentiated into many different cell types of the central nervous system. One challenge when using pluripotent stem cells is to develop robust and efficient differentiation protocols that result in homogenous cultures of the desired cell type. Here, we have utilized the SMAD-inhibitors SB431542 and Noggin in a fully defined monolayer culture model to differentiate human pluripotent cells into homogenous forebrain neural progenitors. Temporal fate analysis revealed that this protocol results in forebrain-patterned neural progenitor cells that start to express early neuronal markers after two weeks of differentiation, allowing for the analysis of gene expression changes during neurogenesis. Using this system, we were able to identify many previously uncharacterized long intergenic non-coding RNAs that display dynamic expression during human forebrain neurogenesis.